Poly(I:C) stimulation is superior than Imiquimod to induce the antitumoral functional profile of tumor‐conditioned macrophages - Maeda, Akihiro (Eur J Immunol, 2019)
Macrophage plasticity is the ability of mononuclear phagocytes to change phenotype, function, and genetic reprogramming upon encounter of specific local stimuli. In the tumor microenvironment, Tumor‐Associated Macrophages (TAMs) acquire an immune‐suppressive and tumor‐promoting phenotype. With the aim to re‐educate TAMs to antitumor effectors, in this study, we used two immunestimulatory compounds: the TLR7 agonist Imiquimod (IMQ) and the TLR3 agonist Poly(I:C). To better mimic in vitro the response of TAMs, we used Tumor‐Conditioned Macrophages (TC‐Mϕ) differentiated in the presence of tumor cell supernatants. Our results show that TC‐Mϕ respond differently from conventional M2‐polarized macrophages. Upon stimulation with IMQ, TC‐Mϕ did not upregulate major histocompatibility complex (MHC II) molecules and unexpectedly expressed increased CD206. With both compounds, TC‐Mϕ produced higher levels of inflammatory cytokines than M2 macrophages. IMQ and Poly(I:C) differed in the types of regulated genes and secreted mediators. Reflecting their signaling pathways, only IMQ significantly induced IL‐1β and IL‐6, while only Poly(I:C) stimulated CXCL10, and both upregulated CCL5. Of note, using a novel cytotoxicity assay, Poly(I:C), but not IMQ, was effective in triggering the cytotoxic activity of TC‐Mϕ against cancer cells. Overall, the results demonstrate that Poly(I:C) stimulation of TC‐Mϕ is superior than IMQ in terms of macrophage re‐education toward antitumor effectors.